The Effect Of Work Discipline, Work Motivation And Teacher Competence On The Performance Of Elementary School Teachers At Sdn 252 Huta Toras Pakantan - Wisnu Rizaldi; Desi Astuti; Yohny Anwar (Universitas Dehasen Bengkulu, 2026)
This study aims to analyze the influence of work discipline, work motivation, and teacher competence on teacher performance at SD 252 Huta Toras Pakantan. This study uses a quantitative approach with a survey method. The population in this study is all teachers of SD 252 Huta Toras Pakantan totaling 40 people, with a sampling technique using total sampling (census). Data was collected through a questionnaire deployment that was compiled based on the indicators of each variable and measured using the Likert scale. The data analysis techniques used include validity test, reliability test, classical assumption test, multiple linear regression analysis, hypothesis test (t test and F test), and determination coefficient (R²) test with the help of SPSS version 22 program. The results of the study showed that partially work discipline, work motivation, and teacher competence had a positive but not significant effect on teacher performance. Work discipline has a significance value of 0.285, work motivation of 0.331, and teacher competence of 0.103, all of which are greater than the significance level of 0.05. However, simultaneously, work discipline, work motivation, and teacher competence had a significant effect on teacher performance with an F-count value of 12.530 and a significance level of 0.000. The Adjusted R Square value of 0.470 indicates that 47.0% of the variation in teacher performance can be explained by the three independent variables, while the rest is influenced by other factors outside of this study.